Entrants to training college : an investigation into the ability in, aptitude for and attitude towards arithmetic and mathematics, displayed by entrants to training colleges for White persons in the Cape Province - Venter, Ian Andri (Rhodes University, Faculty of Education, Department of Education, 1973)
In many cases topics for research are presented to a student in capsulated, clearly defined terms, either as the result of his own experience or as a request by some institution. In other cases the topic takes shape but gradually, very often as the result of a student slowly becoming aware of a field of research through repeated observation of related factors. In some cases the aim of research is to determine whether there is a relationship between various factors; or disprove such in others the main aim may be to prove relationship in unequivocal terms. A large body of research is, however, concerned mainly with the statement of a problem or the finding of facts. The work presented in the following pages can be regarded as falling in the last-mentioned category. A vague suspicion was gradually strengthened by observation and experience until it finally crystallised to form the basis of the research. Facts and figures were gathered and analysed and some conclusions drawn, conclusions that gave rise to more questions and problems than fall within the scope of this work. It was, in fact, found that this research raised more questions than were answered by it and served mainly to underline the magnitude of the problem rather than to offer a solution.
Keywords: Arithmetic -- Study and teaching (Elementary) -- South Africa; Mathematics -- Study and teaching (Elementary) -- South Africa; Mathematics -- Study and teaching (Secondary) -- South Africa